Large variability in plasma efavirenz concentration in Papua New Guinea HIV/AIDS patients associated with high frequency of CYP2B6 516T allele - Natália Bordin Andriguetti; Helena Katherina Van Schalkwyk; Daniel Thomas Barratt; Joseph Tucci; Paul Pumuye; Andrew Alexander Somogyi (Clinical and Translational Science, 2021)
Abstract Papua New Guinea (PNG) has a high HIV/AIDS prevalence and very high frequency of the CYP2B6 c.516G>T (rs3745274) variant. We have conducted the first investigation of the impact of c.516G>T and patient demographics on plasma efavirenz (EFV) and 8‐hydroxyefavirenz (8OH‐EFV) concentrations, metabolic ratio (8OH‐EFV/EFV) (MR), and their association with adverse effects, in PNG patients with HIV/AIDS. For 156 PNG patients with HIV/AIDS taking EFV 600 mg/day (for 3–156 months), plasma EFV and 8OH‐EFV concentrations were quantified, CYP2B6 c.516G>T genotyped, and demographic and self‐reported adverse effects data recorded. Genotype differences in EFV and 8OH‐EFV concentrations, MR, and percent within therapeutic range (1000–4000 ng/ml) were examined, in addition to EFV and 8OH‐EFV concentration differences between patients experiencing adverse effects. CYP2B6 c.516T allele frequency was 53%. Plasma EFV (p < 0.0001), 8OH‐EFV (p < 0.01), and MR (p < 0.0001) differed significantly between genotypes, with genotype explaining 38%, 10%, and 50% of variability, respectively. Plasma EFV concentrations were significantly higher in T/T (median = 5168 ng/ml) than G/G (1036 ng/ml, post hoc p < 0.0001) and G/T (1502 ng/ml, p < 0.0001) genotypes, with all patients above therapeutic range (n = 23) being T/T genotype (p < 0.0001). EFV and 8OH‐EFV concentrations were not significantly higher in patients experiencing adverse effects. In PNG HIV/AIDS population where the 516T frequency is very high, it explains a substantial portion of variability (38%) in EFV disposition; however, at least for the patients receiving EFV long term, this does not translate into significant side effects.